Sole coloration as an unusual aposematic signal in a Neotropical toad - Rößler, Daniela C. (2019)
Many animals have evolved remarkable strategies to avoid predation. In diurnal, toxic harlequin toads (Atelopus) from the Amazon basin, we find a unique colour signal. Some Atelopus populations have striking red soles of the hands and feet, visible only when walking. When stationary, the toads are hard to detect despite their yellow-black dorsal coloration. Consequently, they switch between high and low conspicuousness. Interestingly, some populations lack the extra colour display of the soles. We found comprehensive support that the red coloration can act as an aposematic signal directed towards potential predators: red soles are significantly more conspicuous than soles lacking red coloration to avian predators and the presence of the red signal significantly increases detection. Further, toads with red soles show bolder behaviour by using higher sites in the vegetation than those lacking this signal. Field experiments hint at a lower attack risk for clay models with red soles than for those lacking the signal, in a population where the red soles naturally occur. We suggest that the absence of the signal may be explained by a higher overall attack risk or potential differences of predator community structure between populations. © 2019, The Author(s).